Survival of a surrogate African swine fever virus-like algal virus in feed matrices using a 23-day commercial United States truck transport model - Palowski, Amanda; Balestreri, Cecilia; Urriola, Pedro E.; van de Ligt, Jennifer L. G.; Sampedro, Fernando; Dee, Scott; Shah, Apoorva; Yancy, Haile F.; Shurson, Gerald C.; Schroeder, Declan C. (Frontiers in Microbiology, 2022)
African swine fever virus (ASFV) is a member of the nucleocytoplasmic large DNA viruses (NCLDVs) and is stable in a variety of environments, including animal feed ingredients as shown in previous laboratory experiments and simulations. Emiliania huxleyi virus (EhV) is another member of the NCLDVs, which has a restricted host range limited to a species of marine algae called Emiliania huxleyi. This algal NCLDV has many similar morphological and physical characteristics to ASFV thereby making it a safe surrogate, with results that are applicable to ASFV and suitable for use in real-world experiments. Here we inoculated conventional soybean meal (SBMC), organic soybean meal (SBMO), and swine complete feed (CF) matrices with EhV strain 86 (EhV-86) at a concentration of 6.6 x 107 virus g-1, and then transported these samples in the trailer of a commercial transport vehicle for 23 days across 10,183 km covering 29 states in various regions of the United States. Upon return, samples were evaluated for virus presence and viability using a previously validated viability qPCR (V-qPCR) method. Results showed that EhV-86 was detected in all matrices and no degradation in EhV-86 viability was observed after the 23-day transportation event. Additionally, sampling sensitivity (we recorded unexpected increases, as high as 49% in one matrix, when virus was recovered at the end of the sampling period) rather than virus degradation best explains the variation of virus quantity observed after the 23-day transport simulation. These results demonstrate for the first time that ASFV-like NCLDVs can retain viability in swine feed matrices during long-term transport across the continental United States.